A simple HPLC–MS/MS method for the determination of polymyxin B in human plasma and its application in the pharmacokinetic study in elderly patients infected with multidrug-resistant Gram-negative bacteria - Hu, Sheng; Guo, Nan; Zeng, Juan; Li, Yue; Zhang, Yahui; Jiang, Jinjiao; Leng, Bing; Shen, Chengwu (Frontiers in Pharmacology, 2024)
Polymyxin B (PB) is widely used to treat infections caused by multidrugresistant Gram-negative bacteria. Herein, a simple method to measure the concentration of polymyxin B (PB) in human plasma was developed and validated by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS).PBs was extracted from human plasma by a rapid protein-precipitation method using a 0.1% formic acid (FA) in methanol and then separated on an ultimate AQ-C18 column using linear gradient elution with a 0.5 mL/min flow rate. Subsequently, PB were detected within using a mass spectrometer operated in positive-ion and multiplereaction-monitoring modes. The lower limits of quantification (LLOQ) for PB1 and PB2 were 1.00 and 0.10 μg/mL, respectively. The linear ranges for PB1 and PB2 were 1.00-20.02 and 0.10-2.04 μg/mL, respectively. The validated HPLC-MS/MS method was successfully applied to a study on the pharmacokinetics of PB in elderly patients infected with multidrug-resistant Gram-negative bacteria. PB was administered every 12 hours. Patients receiving a 75 mg maintenance dose had AUC ss, 24 h , and C ss, av values of 117.70 ± 37.03 μg•h/mL and 4.14 ± 1.74 μg/mL, respectively. For patients receiving a 100 mg maintenance dose, these values were 152.73 ± 70.09 μg•h/mL and 5.43 ± 2.85 μg/mL, respectively.